PENERAPAN TEKNIK POSTURAL DRAINAGE DAN BATUK EFEKTIF PADA PASIEN PPOK DENGAN MASALAH BERSIHAN JALAN NAPAS TIDAK EFEKTIF DI RUANG KENANGA RUMAH SAKIT TK II DUSTIRA CIMAHI - Dewi Safariah, Triana; Yunianti, Yuli; Fakhrurozi (Jurnal Kesehatan An-Nuur, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by persistent airflow limitation and chronic respiratory symptoms such as dyspnea and excessive sputum production. Ineffective airway clearance is one of the most common nursing problems in COPD patients due to mucus retention. Postural drainage and effective coughing techniques are non- pharmacological interventions aimed at facilitating sputum removal and improving ventilation. This descriptive case study aimed to describe nursing care through the implementation of postural drainage and effective coughing techniques in a COPD patient with ineffective airway clearance at Kenanga Ward, TK II Dustira Hospital Cimahi. The intervention was carried out twice daily for three consecutive days, with a duration of 20 minutes per session. The evaluation results showed improvement in airway clearance, characterized by decreased adventitious breath sounds (rhonchi and wheezing), reduced respiratory rate, and easier sputum expectoration. It can be concluded that postural drainage and effective coughing techniques can improve airway clearance in COPD patients. These interventions are expected to be applied independently by nurses and families to prevent respiratory complications.